The criminal and social effects of electronic games: A comparative legal jurisprudence study in the light of Saudi law and Islamic law - Al-Jedi, Abdu Ali Muhammad (Journal of Humanities & Social Sciences, 2022)
This research deals with the study of the criminal and social effects of electronic games and the jurisprudential rulings related to them, which are among the new calamities to the Muslim community, trying to identify examples of these games and mentioning the legal ruling on them, with mentioning their harm to Muslim children and youth. The research aimed to achieve a set of goals, including 1- Clarifying what is meant by electronic games, explaining their types and the legal rulings related to each type. 2- Demonstrating the compliance of Islamic law with contemporary issues, and the importance of the topic lies in the fact that it stands on a statement of the criminal and social effects and legal rulings related to electronic games and mentioning the alternative to them. 3- A statement that the Islamic law is keeping pace with emerging and emergency incidents and issues, and that it is valid for every time and place. A- Some of the electronic games cause a waste of money and time, and Islamic law urged the preservation of money and time, and it is also one of the five colleges. B - The health damage caused by some of these games, as previously mentioned, and it is known that the Islamic law came to preserve the human being and his health, and it is one of the five colleges of self-preservation. C- The social damage caused by some of these games. It is well known that Islamic law came to preserve the social fabric of societies.
Keywords: Electronic games; criminal effects; social effects; legal ruling; legal punishment